Comparison of the efficacy of pulsed radiofrequency in treating acute herpetic neuralgia and postherpetic neuralgia in the thoracic segment - Wang, Huan; Zhang, Dandan; Wang, Shiyu; Wang, Hui; Nie, Huiyong (Frontiers in Neurology, 2024)
Objectives This study aimed to compare the efficacy of pulsed radiofrequency (PRF) to dorsal root ganglia (DRG) in treating acute herpetic neuralgia (AHN) and postherpetic neuralgia (PHN) in the thoracic segment. Methods A total of 243 patients with thoracic herpes zoster-related pain (AHN or PHN) from January 2020 to September 2022 were retrospectively analyzed. They were divided into two groups based on the timing of PRF after herpes zoster onset: an acute herpetic neuralgia group (within 90 days) and a postherpetic neuralgia group (more than 90 days). All patients were treated with PRF at the thoracic DRG. The Visual Analog Scale (VAS), the Athens Insomnia Scale (AIS), the Generalized Anxiety Disorder-7 items (GAD-7), and the Patient Health Questionnaire-9 items (PHQ-9) scores were assessed before and at 1 week, 1 month, 3 months, 6 months, and 12 months after surgery, and the results were then compared between the two groups. Results Postoperative scores of VAS, AIS, GAD-7, and PHQ-9 in both groups were significantly lower than preoperative scores (P < 0.001). From 1 month to 12 months after surgery, the AHN group showed significantly lower VAS, AIS, GAD-7, and PHQ-9 scores compared to the PHN group (P < 0.001). In the AHN group, there was a gradual improvement in these scores from 1 week to 12 months post-surgery. Conversely, the PHN group's scores began to worsen slowly from 1 week to 12 months post-surgery. Over time, the difference in scores between the two groups also increased gradually. Conclusion PRF to the DRG is an effective treatment for patients with AHN or PHN who do not respond well to conventional treatments. For AHN patients, PRF to the DRG significantly enhances early pain control, improves sleep and psychological status, and may even prevent the development of PHN.